The Impact of Zoning on Educational Equity in the New Student Admission System - Ika Subandi; Diana Sarah; Evi Wasitoh; Eny Tantia Finorita; Yogi Iskandar; Maman Suryaman (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
The zoning policy in the New Student Admission System is one of the government's strategic steps in creating equal access to and quality of education in Indonesia. This study aims to analyze teachers' perceptions and experiences regarding the implementation of the zoning policy, as well as to evaluate the extent to which the policy has impacted educational equity. The study employs a descriptive qualitative approach, with the subjects being public elementary and secondary school teachers selected through purposive sampling. The research instrument consists of a closed-ended questionnaire using a five-point Likert scale, distributed online via Google Forms. Data were analyzed using Miles and Huberman's interactive analysis technique, which includes data reduction, data presentation, and verification. The results show that teachers understand the objectives of the zoning policy well and support the principle of equitable education. However, its implementation in the field still faces challenges such as infrastructure limitations, uneven teacher distribution, and public perceptions of school quality. Zoning is seen as capable of encouraging schools to improve, but it needs to be supported by more comprehensive and responsive policies tailored to the conditions of each region.